Application of ANFIS, ARIMA and hybrid models in water demand forecasting [electronic resource] - Muhammad Safwan Ibrahim, 1989- (2012)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2012